Does Inflammatory Proteolytic Activity Contribute to the Increased Factor IX Activation Peptide in Men at High Risk of Coronary Heart Disease? A Preliminary Study - Miller, G. J.; Bauer, K. A.; Howarth, D. J.; Mitchell, J. P.; Cooper, J. A. (Thrombosis and Haemostasis, 2002)
In the Second Northwick Park Heart Study, the activation peptides of factor IX (FIXpep) and factor X (FXpep) were measured in 1261 middle-aged men by double-antibody radioimmunoassay. During follow-up 147 men who had a first coronary heart disease (CHD) event were found to have had an increased FIXpep (p = 0.003) and a reduced FXpep (p = 0.05) at baseline compared with those remaining CHD-free (controls). Plasma FIXpep and FXpep were positively associated, but the rate of rise in FIXpep with increasing FXpep was higher in cases than controls (p for interaction = 0.01). In a sample of 87 controls, FIXpep was positively and independently related to the concentrations of a polymorphonuclear-specific fibrinogen degradation product (p = 0.036) and FXpep (p = 0.004), but in larger samples no statistically significant associations were found either with C-reactive protein or with fibrinogen concentration. The findings suggested that the increased FIXpep in men at high CHD-risk may have been partly due to the generation of factor IX inactivation peptides by inflammatory proteolysis and their recognition together with true FIXpep in the radioimmunoassay. Direct evidence for this hypothesis requires development of assays for human elastase-specific factor IX inactivation peptides.
Keywords: Coronary heart disease; factor IX; factor X; activation peptides; fibrinogen degradation product; inflammatory markers